2017
DOI: 10.17079/jkgn.2017.19.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with Feeding Difficulty in Long-term Care Facility Older Adults with Dementia

Abstract: The purpose of this study was to identify feeding difficulties and related factors in older adults with dementia who reside in long-term care facilities. Methods: Participants were 149 older adults with dementia residing in long-term care facilities and 93 certified caregivers working in five long-term care facilities. Data were analyzed using descriptive statistics, t-test, ANOVA, Scheffé test, Pearson correlation coefficient and multiple regression by SPSS 21.0. Results: The mean score for feeding difficult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In a previous study, significant factors that have been shown to influence independent eating performance were considered according to a social ecological model that identified multi-domains related to eating performance, including (a) intrapersonal (resident characteristics), (b) interpersonal (caregiver characteristics), (c) environmental (facility or social culture contexts), and (d) policy (staffing) [ 6 , 11 , 13 ]. In the intrapersonal domain particularly, cognitive status, physical function, comorbidity, and psychological distress have been observed to affect eating behaviors of OAWDs [ 6 , 14 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, significant factors that have been shown to influence independent eating performance were considered according to a social ecological model that identified multi-domains related to eating performance, including (a) intrapersonal (resident characteristics), (b) interpersonal (caregiver characteristics), (c) environmental (facility or social culture contexts), and (d) policy (staffing) [ 6 , 11 , 13 ]. In the intrapersonal domain particularly, cognitive status, physical function, comorbidity, and psychological distress have been observed to affect eating behaviors of OAWDs [ 6 , 14 16 ].…”
Section: Introductionmentioning
confidence: 99%